2022
DOI: 10.3390/met12040621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carrier, Leveller, and Booster Concentrations on Zinc Plating from Alkaline Zincate Baths

Abstract: Organic additives are required for alkaline zincate plating baths to obtain an acceptable coating on steel for corrosion protection. The effects and possible interactions of three commercial additives (Eldiem Carrier, Eldiem Booster, and Bright Enhancer 2× on zinc electrodeposition from a high-concentration alkaline zincate bath were investigated. Visually acceptable deposits were produced within the current density range of 130 to 430 A m−2 for most additive conditions examined. Over concentration ranges exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The throwing power depends on plating parameters such as the zinc concentration, pH, current density, temperature, and plating duration. Some studies have shown that additives can improve the throwing power in non-cyanide zinc plating baths [1]. Figure 13 shows the throwing power (TP (%)) and metal precipitation weight ratio (M) of both cathode specimens according to the composition of the additives added and without additives at a current density of 2 ASD (A/dm 2 ).…”
Section: Throwing Powermentioning
confidence: 99%
See 4 more Smart Citations
“…The throwing power depends on plating parameters such as the zinc concentration, pH, current density, temperature, and plating duration. Some studies have shown that additives can improve the throwing power in non-cyanide zinc plating baths [1]. Figure 13 shows the throwing power (TP (%)) and metal precipitation weight ratio (M) of both cathode specimens according to the composition of the additives added and without additives at a current density of 2 ASD (A/dm 2 ).…”
Section: Throwing Powermentioning
confidence: 99%
“…To prevent corrosion, structural steel must be coated with a less corrosive metal, paint, or enamel. Zinc provides good protection for steel because of its relatively low corrosion rate [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations